DEVELOPMENT OF MEDIA LITERACY OF THE YOUNG GENERATION: A PRACTICAL ASPECT OF THE PROBLEMS - Rudenko , Yuliya; Dehtiarova, Nelya; Petrenko, Serhiy; Horohova, Viktoriya (Physical and Mathematical Education, 2022)
Formulation of the problem. The materials of the article are devoted to the issue of the formation of media literacy of college students. The problem of the insufficient level of media literacy of college students in the conditions of war and the negative consequences of such a state were considered. A strategy for the rapid formation of media literacy is proposed. Materials and methods. The analysis and synthesis of theoretical information were carried out; online testing and survey results were processed. The experimental base of the research: students and teachers of the college of Sumy took part in the experiment. The total number of participants is 97 students and 34 teachers. The results. The article updates the problem of media and information literacy formation of college students in wartime conditions. It is shown that an integral component of any military confrontation is information aggression, which poses a threat to the information security of the country as a whole and each individual. The negative destructive consequences of information wars are highlighted. The need for the formation of media literacy as a vital competence of the individual of the 21st century is substantiated. A direct relationship between the level of media literacy and the ability to resist destructive informational influences and psychological manipulations is proven. The expediency of forming media literacy among young people, as the most vulnerable, due to their age characteristics, and strata of the population, is substantiated. The essence of media literacy is defined from the perspective of the experience of domestic and foreign scientists. The real state of students’ media literacy was analyzed and determined to be insufficient. The tasks for the formation of media literacy for college students, supplemented and changed in the conditions of war, are described. Conclusions. The formation of media literacy is possible according to the following strategy: training of college teachers for the formation of media literacy of students; integration of topics that contribute to the formation of media literacy into educational disciplines; encouragement and support of any media literacy initiatives. Outlined directions for solving the problems of increasing the level of media literacy: training of college teachers for the formation of students’ media literacy; integration of topics that contribute to the formation of media literacy into educational disciplines; encouragement and support of any media literacy initiatives. The urgency of the need for the formation of media literacy determined the finding of effective ways to solve it in the educational environment of colleges. These were: operative training of teachers; integration of media literacy into other disciplines; support for any media educational initiatives of teachers; popularization of media literacy through educational activities; taking online courses on educational platforms. The effectiveness of the selected and implemented ways has been experimentally proven.